Identifikasi Dan Analisis Risiko Pelaksanaan Proyek Jalan Tol Berbasis Severity Index: Studi Kasus Jalan Tol Prabumulih–Muara Enim - Kodrat Insany Taqwim; Firdaus Firdaus; Farlyn Rosyad (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study investigates dominant risks affecting time and cost performance in the Prabumulih–Muara Enim Toll Road Project (Zone 5) within the Trans Sumatra Toll Road corridor. The research adopts an empirical quantitative approach using a two-stage questionnaire and semi-structured interviews involving 24 key project stakeholders selected through purposive sampling. Risk variables were initially compiled from literature, project documents, and preliminary site observations, then validated through a Guttman-scale screening process to ensure contextual relevance. The validated risks were subsequently assessed using the Severity Index (SI) to quantify perceived probability and impact levels, and further mapped into a Probability–Impact Matrix to classify risk criticality and prioritize mitigation. The findings demonstrate that dominant risks emerge not only from technical construction factors but also from managerial coordination, procurement delays, logistical constraints, and safety and quality compliance, which collectively intensify schedule slippage and cost escalation. Methodologically, the integrated SI–PIM framework strengthens risk prioritization by combining structured screening, quantitative severity measurement, and decision-oriented mapping, offering a replicable model for toll road risk governance in large-scale infrastructure projects.